Clean treatment and reuse of cotton mercerizing waste alkali resources using multi-stage evaporation technology - Dawu Shu; Bo Han; Yan Zhang; Jianman Xu; Fangfang An; Wei Zhang; Juchuan Shan; Ruining Liu (Desalination and Water Treatment)
Mercerizing is a key procedure for enhancing the performance of cotton fabrics. However, it has the disadvantages of large wastewater discharge, high alkalinity and difficult treatment. To achieve the recycling of NaOH from mercerizing wastewater, a cleaner recovery system based on multi-stage evaporation was proposed. The properties of different alkali liquors and their applications in bleaching and mercerizing were compared and analyzed. The cooperative enterprises have also evaluated the carbon emission reduction and economic benefits of the recommended system. The results show that the NaOH concentration was increased by 2 times after the mercerizing waste alkali was treated. Compared to NaOH, the whiteness of cotton fabric bleached with recycled alkali decreased by 6.0% ∼ 8.7%, mainly due to the ineffective decomposition of hydrogen peroxide. The cotton fabric mercerized with recovered alkali exhibits a crystallinity of 52.7%, a barium value of 220, and a capillary effect of 8.5 cm/30 min. These values meet the production requirements of the textile industry. The recovery system can recover 57.68 t of mercerization waste liquid, save 9.88 t of 32% NaOH solution, 45 t of water and 3.92 t of 98% sulfuric acid per day. Compared to the conventional process, the system not only reduces energy consumption and pollutant discharge at their source, but also improves the utilization rate of water resources and chemicals.